O aconselhamento pastoral e a sua abordagem em pacientes oncológicos: da crise à intervenção - Rodrigues, Rafael Souza (2012)
The present study aims to reflect on the contributions of pastoral counseling, with emphasis on spirituality in cancer patients. Cancer is a disease that can bring a moment of crisis and seriously affect all areas of a person's life. Thus, it is pertinent to present some definitions and types of crises, as well as the nature and the dynamic processes involving a crisis. In this study, this is done throught the pastoral counseling and in the seeking for biblical references for the crisis. It is also necessary to understand the cancer in its general aspects and analyze how this disease that affects a growing number of people, causes several changes in the patient and in his family. At the end of the study three models of pastoral counseling that preconize spiruality in crisis situations are discussed, such models are: the Gary Collins models, Howard Clinebell, designed in the North American context and the model of Daniel Schipani, based on the Latin American reality. In addition, we describe an example of pastoral counseling in a hospital setting. In their different visions, the pastoral counseling models surveyed provide important support to assist faith communities to fulfill its mission that is to serve others, throught the support to cancer patients.